2014
DOI: 10.9775/kvfd.2014.10692
|View full text |Cite
|
Sign up to set email alerts
|

Simental Bir Buzağıda Görülen Çoklu Konjenital Anomaliler

Abstract: ÖzetBu olgu sunumunda; Simental bir buzağıda gözlenen çoklu konjenital anomaliler tanımlandı. Şekillenen anomalilerin çoğunlukla iskelet sisteminde yer aldığı saptandı. Buzağının ön ve arka bacak kemiklerinde çeşitli morfolojik bozukluklar ile birlikte bu kemiklere ait eklemlerin tamamında arthrogryposis şekillendiği gözlemlendi. İskelet sistemi dışındaki en önemli anomali; kalın bağırsaklarda caecum'dan önce, caecum'a benzer ve onunla aynı noktaya açılan bir bağırsak segmentinin daha mevcut olması idi. Kalpte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Transthoracic echocardiography was performed as a gold standard for definitive diagnosis. VSD to Ao diameter ratio (0.74) was greater than 0.6 suggestive for large, unrestrictive VSD [8] .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Transthoracic echocardiography was performed as a gold standard for definitive diagnosis. VSD to Ao diameter ratio (0.74) was greater than 0.6 suggestive for large, unrestrictive VSD [8] .…”
Section: Discussionmentioning
confidence: 95%
“…Congenital cardiac defects such as ASD and membranous VSD and their relation with breed and sex predispositions were reported previously in calves [1][2][3][4][6][7][8][9] , but the diagnostic steps and cardiopulmonary by-pass procedures of a combination of three congenital cardiac defects (ASD, VSD and PDA) in newborn calves has not been reported yet.…”
Section: Discussionmentioning
confidence: 99%
“…The cause of defects in the intestines of animals is ischemia, which usually occurs in a segment of the intestine in the early stages of fetal life (Azizi et al 2010;Jubb et al 1993). Intestinal atresia is the most common in domestic animals and the most common intestinal anomalies in ruminants are atresia coli, atresia ani, atresia recti (Demiraslan et al 2014;Göksel and Saritaş 2015;Jubb et al 1993). It has been reported that atresia ani is inherited in cattle, atresia jejuni is an autosomal disease in Highland cattle and Jersey breeds, but atresia coli is not genetically understood (Prieur and Dargatz 1984) and segmental intestinal agenesis is rarely reported (Prieur and Dargatz 1984).…”
Section: Introductionmentioning
confidence: 99%